Distribution of residential Plots of land and its impact on urban growth in the City of Kut - dr. Ali Fawzi Saeed (Journal of College of Education, 2024)
Urban growth is a distinct phenomenon of the continuous growth of a city as a result of economic , political and social changes . City centers are among the areas most exposed to change and growth because they contain Various urban functions . Urban growth is the increase in urban land areas as a result of the in crease in the population of cities .             Urban growth may take different patterns , including random and planned patterns . There fore , government policy seeks to adopt planned urban growth according to specific goals . The government is working to achieve this through the process of distributing residential plots of land in specific locations and spaces according to government policy in directing the expansion of urban growth in the city .            The research also dealt with clarifying the concept of urban growth , the factors affecting it , and the different urban growth patterns , as well as explaining the impact of the distribution of residential lands on the growth of the city by determining the number of plots distributed for the period ( 2013 – 2023 ) their location and area , and the segments benefiting from them .
Keywords: Urban growth, Residential lands